A Novel Sensing Device for Assessing Underground Cable Condition (International Journal of Food and Nutritional Sciences, 2022)
Electricity companies have invested in millions of kilometres of low-voltage underground cables that since 1950s in an attempt to make secondary power distribution more dependable and resilient. Early cabling techniques employed butyl rubber-insulated wires and journal article lead covered cables. The insulation has become less effective with time and heat, leading to catastrophic failures and underground fires that might harm the public and workers, destroy property, and cause protracted power outages. It is expensive to evaluate the condition of underground cables. The bulk of testing techniques need power interruptions, are intrusive (high voltages are utilised to create partial discharges), and destructive (invasive) (cables must be removed). This article describes a novel active clamp assessment method that accurately determines the insulation status of underground cables. It is not harmful, obtrusive, or invasive. In order to prioritise cable replacement, simple tests provide precise condition assessments. It's called a cable failure prediction system.